Review : Gastropods As A Bioindicator and Biomonitoring Metal Pollution - Samsi, Andi Nur; Asaf, Ruzkiah; Sahabuddin, Sahabuddin; Santi, Andi; Wamnebo, Muhammad Ikhsan (Aquacultura Indonesiana, 2017)
Water pollution effect on aquatic organisms and if consumed can affect people's health. These pollutants can be heavy metals such as Cd, Pb, Cr, Hg, and others. Heavy metals have high levels will cause disorders of the kidneys, brain, severe irritation to the skin, can cause diarrhea and even death. The purpose of this paper is to explain physiological mechanisms that occur in the body of gastropods are linked to pollutants in the water environment. Therefore, monitoring the level of pollution a body of water that is alleged to have suffered contamination is very important. Gastropods are one of the aquatic animals (Class) used as bioindicators and biomonitoring for this group of animals has a high ability to accumulate heavy metals in their bodies compared to other aquatic animals. Gastropods is one bioavailability against metal pollution so that it can be used for environmental monitoring. Littoraria scabra, Nassarius reticulatus, Nerita albicilla, Nucella lapillus, Gibberulus gibbosus, Terebralia palustris, and Telescopium telescopiun always use as biomonitoring metal pollution. The main indicator that can be shown by gastropods is declining abundance and body size. Other indicators are as bioavailability of heavy metals in the soft tissues and shells. The ability of the heavy metal deposits is influenced by environmental factors, body size, weight, and gender. Heavy metals can affect hard, thickness, volume, and color of the shell.